Status of Safety Culture of Psychiatric Patients from The Viewpoint of Medical Personnel - Peyvand Bastani; Mohammad Ghasem Nezhad; Ali Reza Yusefi; Ahmad Sadeghi (Tehran University of Medical Sciences, 2018)
Background: One of the main components of the quality of health services is patient safety. This study aimed to determine safety culture status of psychiatric patients from the viewpoint of the medical staff of Ibn Sina and Hafez hospitals in Shiraz.   Materials and Methods: This descriptive-analytic study performed as a cross-sectional one in 2017. The study population included 165 health care personnel of the hospitals which were selected by census sampling. The study tool was a standard questionnaire for the hospitalchr('39')s safety culture. Data were analyzed using descriptive statistics and independent t-test, ANOVA, Pearson correlation coefficient and multivariate linear regression using SPSS version 23 software at a significant level of α = 5%.   Results: The average of safety status of the patients calculated 154.62 ± 19.74. The patient safety culture was estimated at an acceptable level (64.1%). The dimensions of personnel affairs (36%) and non-punitive responses to errors (34.7%) were in an unfavorable situation. There was a significant association between the employment status of personnel and patient safety (P<0.05).   Conclusion: Despite the acceptable condition of the patientchr('39')s safety culture, however, the dimensions of the non-responsive response to the mistakes and issues related to the personnel were in an unfavorable situation and require prompt and appropriate actions. It is suggested that hospital authorities to provide the necessary interventions including cultures for reporting of errors, organizing comprehensive training programs, and continuously improving the clinical governance system.